The influence of compensation on employee achievement - Suprayitno, Nur Fadillah; Abbas Akbar , Subhan; Wulandari, Sri; Aryni, Nurul (Trigin Publisher, 2024)
The purpose of this research is to determine the effect of compensation on employee work performance at PT Bank Syariah Indonesia, Tbk Cabang Soppeng. Determining the sample used a saturated sampling technique, which is a sampling technique by taking the entire population as a sample, so that the sample in this study was all employees of PT Bank Syariah Indonesia, Tbk, Cabang Soppeng, totaling 32 people. To determine the effect of compensation on work performance, simple linear regression analysis was used. The results of the research show that the significance value is 0.049 <0.05, so it can be seen that compensation has an effect on employee work performance at PT Bank Syariah Indonesia, Tbk Cabang Soppeng